(untitled) (Interdisciplinary Studies Journal, 2026)
This study examines how conceptual decolonization can foster the construction of original philosophical categories rooted in african cultural traditions and systems of thought. It starts from the premise that african philosophy has historically been disqualified by an epistemology that privileges western standards of rationality and excludes other forms of thinking. The research adopts a theoretical-interpretative approach, drawing on the thought of Kwasi Wiredu – particularly his formulation of conceptual decolonization, as discussed in the specialized literature – to address the coloniality of knowledge and its philosophical implications. The plurality of expressions of coloniality – existential, political, cultural, and epistemological – is acknowledged, with the analysis focusing on the latter. The discussion is driven by the persistence of stereotypes associating africans with irrationality, non-philosophical orality, and the absence of systematic thought – elements that continue to sustain the epistemic devaluation of the continent. The article is organized into three axes: the origins and meanings of conceptual decolonization in philosophical debate; its critical and reconstructive dimensions as a challenge to eurocentrism; and the role of language as an instrument of in(ex)clusion in african knowledge. It concludes that conceptual decolonization constitutes a strategic epistemological category for adapting and reconfiguring eurocentric conceptual entanglements to african realities.